A QUALITATIVE ANALYSIS OF CITILINK PASSENGER SELF CHECK-IN AT SAM RATULANGI INTERNATIONAL AIRPORT - Koloay, Kevin C.; Pandowo, Merinda Ch. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract: Many airlines have a self-check-in process allowing passengers with bags to check-in at the self-service kiosks with luggage up to approximately 20kgs and 30 minutes prior to departure time. Nowadays Citilink offer the ease of check-in to it is customer through self check-in machine at Sam Ratulangi International Airport located in front of the check-in counter zone which usually served by Citilink employee. The objectives of this research are to know the self check-in service of Citilink at Sam Ratulangi International Airport. To achieve these objectives the researcher got information from 10 respondent using qualitative studies which is in-depth interview. The result of the research shows that the self-check in Citilink at Sam-Ratulangi Airport has positif respon based on the answer of the respondent, Self check-in services at Sam ratulangi Airport is already good, all the respondent that have been using it very happy with the existence of self check-in services, because self check-in service that provide by the citilink is very helpful and useful for all the passenger because the passenger can save more time, do not need to queuing at the manual counter and also the self check-in is very simple, for the machine of the self check-in it is easy to use and easy to understand. The recommendation for Citilink is keep maintain and improve the service to be more good.Â Keywords: self-check in, citilink, sam-ratulangi airport, services